Eileen Gray's Photography. An Architectural Journey through E.1027 - González Jiménez, Beatriz S.; Ruiz Colmenar, Alberto (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
This text proposes an analysis of the photographical dossier that Eileen Gray prepared on E.1027, her best-known project. Far from assuming a simple compilation of unconnected images, the report was conceived from its origin as an architectural journey, made up of photographs carefully taken by the architect herself. In them, the space and the objects were part of a scenography designed to generate a visual tour of the portrayed scene. The aim of this article is to recover this dossier published in 1929 by the magazine l'Architecture Vivante, showing the personal vision that Eileen Gray developed of her own house. Likewise, the aim is to analyze Gray’s outstanding facets as an architect, a designer, and a photographer.
Keywords: l’Architecture Vivante; Photography; Storytelling; Domestic space; Gender; Women Architects